The fetomaternal interface in the placenta of three species of armadillos (Eutheria, Xenarthra, Dasypodidae) - Barbeito, Claudio Gustavo (2012)
Background: Placental characters vary among Xenarthra, one of four supraordinal clades of Eutheria. Armadillos are known for villous, haemochorial placentas similar to humans. Only the nine-banded armadillo has been well studied so far. Methods: Placentas of three species of armadillos were investigated by means of histology, immunohistochemistry including proliferation marker, and transmission and scanning electron microscopy. Results: The gross anatomy differed: Euphractus sexcinctus and Chaetophractus villosus had extended, zonary placentas, whereas Chaetophractus vellerosus had a disk. All taxa had complex villous areas within the maternal blood sinuses of the endometrium. Immunohistochemistry indicated the validity of former interpretations that the endothelium of the sinuses was largely intact. Tips of the villi and the columns entering the maternal tissue possessed trophoblast cell clusters with proliferation activity. Elsewhere, the feto-maternal barrier was syncytial haemochorial with fetal vessels near the surface. Conclusions: Differences among armadillos occurred in regard to the extension of the placenta, whereas the fine structure was similar. Parallels to the human suggest that armadillos are likely to be useful animal models for human placentation